A race against time: monitoring the necropolis and the territory of Cyrene and Giarabub through protocols of remote sensing and collaboration with Libyan colleagues. (28th September 2017) - Menozzi, Oliva; Di Valerio, Eugenio; Tamburrino, Clara; Shariff, Abdulrahim Saleh; d'Ercole, Vincenzo; Di Antonio, Maria Giorgia
Abstract: The core area of Cyrene, despite recent upheavals, benefits from well-managed controls and fences that so far seem to have stopped the looting, although not the vandalism. These fences act mainly as a psychological barrier; for the local people, everything inside the fences is seen as 'more important' than what is outside. However, it is impossible to enclose all the monumental tombs, rock-cut sanctuaries and ancient farms and fortifications. The first type of damage we see is due to looting, which is increasing, and acts of vandalism. The lack of regulation and police control as well as increased urbanisation have caused a lot of uncontrolled building, causing the further destruction of large sections of the necropolis. A second type of damage is due to the lack of maintenance. In order to help restore the sites, the Universities of Urbino, Chieti, Roma 3, Naples 2 and the Mission of the MIBACT at Giarabub, in collaboration with the DoA, have organised courses on 'Rescue restoration in emergency'. Despite the growing number of inspectors and technicians in Cyrene, there are still not enough archaeologists, guards or restorers. This paper explains these general issues and, as a case study, the remote but important area of Giarabub. Abstract : تستفيد منطقة مركز القيروان من الضوابط والأسيجة المُحكمة الإدارة بالرغم من الاضطرابات الحديثة، مما أوقف النهب ولكن ليس التخريب . يعمل السياج كرادع نفسي بشكل رئيسي : بالنسبة للسكان المحليين فإن أي شيء داخل السياج يعتبر أكثر أهمية مما هو خارجه . ولكن من المستحيل تسييج جميع القبور الضخمة والمقدسات المحفورة بالصخر والمزارع القديمة والتحصينات . أول أنواع الضرر الذي نشاهده هو بسبب النهب المتزايد والأعمال التخريبية . إن إفتقار تطبيق القوانين وعدم سيطرة الشرطة والعمران المتزايد قد سببوا وجود العديد من الأبنية غير المضبوطة، مما سبب مزيداً من الدمار لأجزاء كبيرة من المقابر. والنوع الثاني من الدمار يعود إلى نقص الصيانة. من أجل المساعدة في ترميم المواقع، فقد نظمت جامعات إربينو وكييتي وروما 3 ونيابلز 2 وبعثة وزارة التراث الثقافي والأنشطة والسياحة في جغبوب وبالتعاون مع دائرة الآثار، دورات في "الترميم الإنقاذي في حالات الطوارئ ". وبالرغم من العدد المتزايد للمفتشين والتقنيين في القيروان، لا يوجد العدد الكافي من علماء الآثار والحراس والمرممين. هذه الورقة تشرح هذه المواضيع العامة وكحالة دراسة، تشرح عن منطقة جغبوب الهامة على الرغم من بعدها.